Preparation method and application of sodium-ion battery hard carbon negative electrode material with rich closed-pore structure

By filling the asphalt in the porous carbon holes and performing high-temperature carbonization treatment, the hard carbon closed-pore structure is solved, and the problems of small capacity and high production cost of hard carbon anode material platform of sodium ion battery are achieved, and efficient sodium storage performance and low-cost industrial production are achieved.

CN119503763APending Publication Date: 2025-02-25BEIJING UNIV OF CHEM TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411153257.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The hard carbon anode material of sodium ion battery has problems such as small platform capacity, low Coulomb efficiency for the first time and high production cost. The existing preparation methods are complex and are not conducive to industrialization.

Method used

Asphalt and porous carbon are used as raw materials, and the porous carbon holes are filled in the porous carbon openings through asphalt and carbonized at high temperature to construct a hard carbon closed-porous structure, thereby increasing the platform capacity of porous carbon.

Benefits of technology

By improving the microstructure of the material, the first Coulomb efficiency and reversible capacity are improved, the sodium storage performance is improved, and the production cost is reduced, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503763A_ABST
    Figure CN119503763A_ABST
Patent Text Reader

Abstract

The invention relates to preparation of a sodium-ion battery negative electrode material, and discloses a preparation method and application of a sodium-ion battery hard carbon negative electrode material with a rich closed-pore structure. Porous carbon with a high specific surface area (more open pores) is modified by asphalt, and the modified hard carbon negative electrode material has fewer open pores and abundant closed pores, so that the low voltage (lt) of the negative electrode material can be greatly improved; 0.1 V) platform capacity, and the first coulombic efficiency of the negative electrode material is also effectively improved. The preparation method has the characteristics that the raw material asphalt is low in cost and easy to obtain, the carbon product yield is high, the preparation process method is simple, environment-friendly and the like, and large-scale industrial production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sodium ion battery hard carbon negative electrode materials, and in particular to a method for preparing a sodium ion battery hard carbon negative electrode material with a rich closed-pore structure. Background Art

[0002] The global demand for traditional energy has led to a series of environmental and energy crises, and it is urgent to explore sustainable and cost-effective energy storage technologies. Lithium-ion batteries are widely used due to their high energy density and long life, but due to the shortage of lithium resources, high costs, and safety issues of lithium-ion batteries, lithium-ion batteries cannot fully meet the needs of large-scale electrochemical energy storage.

[0003] Sodium-ion batteries have the advantages of abundant resources, low cost, high safety, and similar working principles to lithium-ion batteries, and are considered to be an effective alternative to lithium-ion batteries. At present, hard carbon is considered to be the most commercially promising negative electrode material for sodium-ion batteries. However, it faces constraints such as small platform capacity, low initial coulombic efficiency, and high production costs. According to the sodium storage mechanism shown by current research, sodium ions can be stored in the closed pores of hard carbon materials in the form of quasi-metallic sodium clusters, providing capacity in the platform area. Therefore, how to reasonably adjust the microstructure and prepare hard carbon negative electrode materials with rich closed-pore structures has become a hot research direction in the field of sodium-ion batteries. At present, the methods for preparing the closed-pore structure of hard carbon negative electrode materials include: one is to directly treat the biomass precursor with a porous structure at high temperature, so that the carbon microcrystals expand when heated, resulting in pore contraction and pore volume reduction, and obtain hard carbon with abundant closed pores; another is to first prepare porous carbon by template method or activation method, and then treat it at high temperature, so that the open pores shrink into closed pores at high temperature; another method is carbon coating closed pore method, which refers to adding suitable coating materials to the existing porous carbon to block the open pores on its surface, thereby forming a large number of closed pores to increase the sodium storage capacity. In patent CN118239487A, porous hard carbon is used as the matrix material, and the chemical vapor deposition method is used to deposit carbon into relatively large micropores. As the deposition time increases, after some pores are deposited, they will gradually continue to deposit on the surface of the hard carbon to form a soft carbon coating layer with a pinned structure. However, the CVD process is too complicated and requires special equipment. In addition, the amount of carbon source is difficult to accurately control, and the industrialization cost is high and the safety is low. Summary of the invention

[0004] The present invention provides a method for preparing a sodium ion battery hard carbon negative electrode material with a rich closed-pore structure according to the problem to be solved. Asphalt and porous carbon are used as raw materials, asphalt is filled in the open pores of the porous carbon, and a hard carbon closed-pore structure is constructed during high-temperature carbonization, effectively converting the open pores into closed pores, thereby increasing the platform capacity of the porous carbon. The preparation method has the characteristics of low cost and easy acquisition of raw asphalt, high yield of carbon products, simple preparation process, and environmental friendliness, which is conducive to large-scale industrial production.

[0005] The preparation steps of a sodium ion battery hard carbon negative electrode material with rich closed-pore structure are as follows:

[0006] Step (1) weighing a certain amount of asphalt, crushing it, adding the asphalt into a solvent and stirring it for a period of time to fully dissolve it in the solvent;

[0007] Step (2) adding porous carbon in a certain proportion to the suspension prepared in step (1) and stirring for a period of time;

[0008] Step (3) removing the solvent from the suspension prepared in step (2) and drying it to obtain a precursor;

[0009] Step (4) subjecting the precursor obtained in step (3) to high-temperature carbonization treatment in an inert atmosphere, wherein the carbonization temperature is 1000° C.-1800° C., and a hard carbon negative electrode material having a rich closed-pore structure is obtained after high-temperature treatment.

[0010] Preferably, the asphalt in step (1) is one or more of low-temperature coal asphalt, medium-temperature coal asphalt, high-temperature coal asphalt, petroleum asphalt, and mesophase asphalt.

[0011] Preferably: the porous carbon in step (2) has a specific surface area of ​​800 m 2 g -1 -3500m 2 g -1 , one or more porous carbons with a micropore content greater than 40%, the mass ratio of asphalt to porous carbon is 1: (1-5), and the stirring time is 6h-48h.

[0012] Preferably, the inert atmosphere in step (4) is argon, and the heating rate is 2-5°C / min.

[0013] Beneficial Effects of the Invention

[0014] The negative electrode material provided by the present invention is prepared by filling asphalt in the porous carbon openings, and high-temperature carbonization to convert the surface openings into closed pores, thereby reducing structural defects and improving the regularity of the carbon layer, thereby hindering a part of irreversible sodium adsorption, inhibiting the decomposition of the electrolyte, and reducing the occurrence of side reactions, thereby improving the first coulomb efficiency and reversible capacity, and further improving the sodium storage performance of the material. The preparation method has the characteristics of low cost and easy acquisition of raw asphalt, high yield of carbon products, simple preparation process, and environmental friendliness, and is conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Scanning electron microscope image of the carbonized sample of Comparative Example 1;

[0016] Figure 2 Small angle X-ray scattering patterns of the samples of Comparative Example 1 and Example 7;

[0017] Figure 3 The charge and discharge curves of the samples of Comparative Example 1 and Example 7. DETAILED DESCRIPTION

[0018] The present invention is further described below by way of specific embodiments, but is not intended to limit the present invention.

[0019] Embodiment 1:

[0020] (1) Weigh 5 g of medium-temperature coal tar pitch and grind it, then add the medium-temperature coal tar pitch into tetrahydrofuran and stir for a period of time to fully dissolve it in tetrahydrofuran.

[0021] Step (2) 1 g of commercial activated carbon 1 having a specific surface area of ​​1780 m 2 / g, with a micropore content of 43.7%, was added to the suspension prepared in step (1) and stirred for 6 hours.

[0022] Step (3) The suspension prepared in step (2) is evaporated in an oil bath to remove the tetrahydrofuran therein, and then placed in a vacuum oven for vacuum drying to obtain a precursor.

[0023] Step (4) The precursor obtained in step (3) is subjected to high-temperature carbonization treatment in an inert atmosphere, the carbonization temperature being 1000° C., and a hard carbon negative electrode material is obtained after high-temperature treatment.

[0024] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 186 mAh g -1 .

[0025] Embodiment 2:

[0026] (1) Weigh 3 g of medium-temperature coal tar pitch and grind it, then add the medium-temperature coal tar pitch into tetrahydrofuran and stir for a period of time to fully dissolve it in tetrahydrofuran.

[0027] Step (2) 1 g of commercial activated carbon 1 having a specific surface area of ​​1780 m 2 / g, micropore content 43.7%, added to the suspension prepared in step (1), 18h.

[0028] Step (3) The suspension prepared in step (2) is evaporated in an oil bath to remove the tetrahydrofuran therein, and then placed in a vacuum oven for vacuum drying to obtain a precursor.

[0029] Step (4) The precursor obtained in step (3) is subjected to high-temperature carbonization treatment in an inert atmosphere, the carbonization temperature being 1000° C., and a hard carbon negative electrode material is obtained after high-temperature treatment.

[0030] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 206 mAh g -1 .

[0031] Embodiment 3:

[0032] (1) Weigh 2 g of medium-temperature coal tar pitch and grind it, then add the medium-temperature coal tar pitch into tetrahydrofuran and stir for a period of time to fully dissolve it in tetrahydrofuran.

[0033] Step (2) 1 g of commercial activated carbon 1 having a specific surface area of ​​1780 m 2 / g, with a micropore content of 43.7%, was added to the suspension prepared in step (1) and stirred for 18 hours.

[0034] Step (3) The suspension prepared in step (2) is evaporated in an oil bath to remove the tetrahydrofuran therein, and then placed in a vacuum oven for vacuum drying to obtain a precursor.

[0035] Step (4) The precursor obtained in step (3) is subjected to high-temperature carbonization treatment in an inert atmosphere, the carbonization temperature being 1500° C., and a hard carbon negative electrode material is obtained after high-temperature treatment.

[0036] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 235mAhg -1 .

[0037] Embodiment 4:

[0038] (1) Weigh 1 g of medium-temperature coal tar pitch and grind it, then add the medium-temperature coal tar pitch into tetrahydrofuran and stir for a period of time to fully dissolve it in tetrahydrofuran.

[0039] Step (2) 1 g of commercial activated carbon 1 having a specific surface area of ​​1780 m 2 / g, with a micropore content of 43.7%, was added to the suspension prepared in step (1) and stirred for 24 hours.

[0040] Step (3) The suspension prepared in step (2) is evaporated in an oil bath to remove the tetrahydrofuran therein, and then placed in a vacuum oven for vacuum drying to obtain a precursor.

[0041] Step (4) The precursor obtained in step (3) is subjected to high-temperature carbonization treatment in an inert atmosphere, the carbonization temperature being 1800° C., and a hard carbon negative electrode material is obtained after high-temperature treatment.

[0042] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 216 mAh g -1 .

[0043] Embodiment 5:

[0044] (1) Weigh 2 g of mesophase pitch and grind it, then add the mesophase pitch into tetrahydrofuran and stir it for a while to fully dissolve it in tetrahydrofuran.

[0045] Step (2) 1 g of commercial activated carbon 2, with a specific surface area of ​​2428.42 m 2 / g, with a micropore content of 79.8%, was added to the suspension prepared in step (1) and stirred for 24 hours.

[0046] Step (3) The suspension prepared in step (2) is evaporated in an oil bath to remove the tetrahydrofuran therein, and then placed in a vacuum oven for vacuum drying to obtain a precursor.

[0047] Step (4) The precursor obtained in step (3) is subjected to high-temperature carbonization treatment in an inert atmosphere, the carbonization temperature being 1800° C., and a hard carbon negative electrode material is obtained after high-temperature treatment.

[0048] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 271 mAh g -1 .

[0049] Embodiment 6:

[0050] (1) Weigh 1 g of high-temperature coal tar and grind it, then add the high-temperature coal tar into tetrahydrofuran and stir for a while to fully dissolve it in tetrahydrofuran.

[0051] Step (2) 1 g of commercial activated carbon 3, with a specific surface area of ​​1959.21 m2 / g, with a micropore content of 85.2%, was added to the suspension prepared in step (1) and stirred for 48 hours.

[0052] Step (3) The suspension prepared in step (2) is evaporated in an oil bath to remove the tetrahydrofuran therein, and then placed in a vacuum oven for vacuum drying to obtain a precursor.

[0053] Step (4) The precursor obtained in step (3) is subjected to high-temperature carbonization treatment in an inert atmosphere, the carbonization temperature being 1500° C., and a hard carbon negative electrode material is obtained after high-temperature treatment.

[0054] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 296 mAh g -1 .

[0055] Embodiment 7:

[0056] (1) Weigh 2 g of high-temperature coal tar pitch and grind it, then add the high-temperature coal tar pitch into tetrahydrofuran and stir for a period of time to fully dissolve it in tetrahydrofuran.

[0057] Step (2) 1 g of commercial activated carbon 3, with a specific surface area of ​​1959.21 m 2 / g, with a micropore content of 85.2%, was added to the suspension prepared in step (1) and stirred for 48 hours.

[0058] Step (3) The suspension prepared in step (2) is evaporated in an oil bath to remove the tetrahydrofuran therein, and then placed in a vacuum oven for vacuum drying to obtain a precursor.

[0059] Step (4) The precursor obtained in step (3) is subjected to high-temperature carbonization treatment in an inert atmosphere, the carbonization temperature being 1400° C., and a hard carbon negative electrode material is obtained after high-temperature treatment.

[0060] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 313 mAh g -1 The nitrogen adsorption / desorption test showed that the specific surface area of ​​the negative electrode material in this example was only 13m 2 / g. Through the small angle test, the precursor prepared in step (3) has no nanopores, but nanopores appear after high temperature carbonization.

[0061] Embodiment 8:

[0062] (1) Weigh 2 g of low-temperature coal tar, grind it, add it into tetrahydrofuran and stir it for a while to make it fully dissolved in tetrahydrofuran.

[0063] Step (2) 1 g of commercial activated carbon 2, with a specific surface area of ​​2428.42 m 2 / g, micropore content of 79.8%, the microporous porous carbon was added to the suspension prepared in step (1) and stirred for 24 hours.

[0064] Step (3) The suspension prepared in step (2) is evaporated in an oil bath to remove the tetrahydrofuran therein, and then placed in a vacuum oven for vacuum drying to obtain a precursor.

[0065] Step (4) The precursor obtained in step (3) is subjected to high-temperature carbonization treatment in an inert atmosphere, the carbonization temperature being 1500° C., and a hard carbon negative electrode material is obtained after high-temperature treatment.

[0066] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 296 mAh g -1 .

[0067] Comparative Example 1: Commercial activated carbon 2, with a specific surface area of ​​2428.42 m 2 / g, micropore content of 79.8%, and high-temperature carbonization at 1400℃ was directly carried out under inert atmosphere.

[0068] The electrochemical performance test results show that the electrode material has a -1 The discharge capacity at the current density can reach 105 mAh g -1 The nitrogen adsorption / desorption test shows that the specific surface area of ​​the negative electrode material of this example is 1856m 2 / g.

[0069] According to the above test data, it can be seen that the materials of Examples 1-10 at 1500°C have been significantly improved in the first charge and discharge specific capacity, platform capacity and first coulombic efficiency. Figure 3 This shows that the porous carbon itself has a rich pore structure. After asphalt impregnation, the nanopores disappear. After high-temperature carbonization, the nanopores reappear, and the specific surface area decreases. This shows that the open pores of the sample modified with asphalt are transformed into closed pores, which not only increases the platform capacity but also reduces surface defects and improves the first coulomb efficiency.

[0070] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Any equivalent changes and modifications made on the basis of the claims of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing a sodium ion battery hard carbon negative electrode material with a rich closed-pore structure, the steps of which are as follows: (1) Weigh a certain amount of asphalt, crush it, add it into a solvent and stir it for a period of time to make it fully dissolved in the solvent; (2) adding porous carbon in a certain proportion to the suspension prepared in (1) and stirring for a period of time; (3) removing the solvent from the suspension prepared in (2), drying it, and obtaining a precursor; (4) The precursor obtained in (3) is subjected to high-temperature carbonization treatment in an inert atmosphere at a carbonization temperature of 1000° C.-1800° C., and a hard carbon negative electrode material with a rich closed-pore structure is obtained after high-temperature treatment.

2. The preparation method according to claim 1, wherein the asphalt in step (1) is one or more of low-temperature coal tar, medium-temperature coal tar, high-temperature coal tar, petroleum asphalt, and mesophase asphalt.

3. The preparation method according to claim 1, wherein the porous carbon in step (2) is carbon with a specific surface area of ​​800 m 2 g -1 -3500m 2 g -1 , one or more porous carbons with a micropore content higher than 40%, the mass ratio of asphalt to porous carbon is 1: (1-5), and the stirring time is 6h-48h.

4. The preparation method according to claim 1, wherein the inert atmosphere in step (4) is argon and the heating rate is 2-5°C / min.

5. Asphalt-modified activated carbon is characterized in that the asphalt-modified activated carbon contains the preparation method described in any one of claims 1 to 4.

6. The asphalt-modified activated carbon prepared according to any one of claims 1 to 5 is used as a negative electrode material for sodium ion batteries.

Citation Information

Patent Citations

  • Method for preparing hard carbon negative electrode material rich in closed pores from porous carbon and application of hard carbon negative electrode material

    CN118239487A